Penerapan Metode CPM dan PERT pada Sistem Informasi Manajemen Proyek Pembuatan Website Akreditasi dan Mutu Fakultas Sains dan Teknologi UIN Imam Bonjol Padang - Yaslinda Lizar; Ummi Rosmita (Justek : Jurnal Sains dan Teknologi, 2024)
Abstract: The Faculty of Science and Technology of UIN Imam Bonjol Padang is preparing for institutional and study program accreditation. One of the requirements is the provision of a complete accreditation and quality website. To ensure timely completion, the website project needs careful planning. This research applies the Critical Path Method (CPM) and Program Evaluation and Review Technique (PERT) to management information systems for planning and scheduling accreditation website projects. CPM is used to determine the set of critical project activities while PERT calculates the probabilistic project duration. The application results show that the information system is able to help the accreditation website project management to be completed according to the deadline. In addition to planning and scheduling features, the system is equipped with a module for monitoring and evaluating project achievements. By applying CPM and PERT to the project management information system, project planning and control become more directed and reliable.Abstrak: Fakultas Sains dan Teknologi UIN Imam Bonjol Padang tengah mempersiapkan akreditasi institusi dan program studi. Salah satu persyaratan adalah penyediaan website akreditasi dan mutu yang lengkap. Untuk memastikan pengerjaan tepat waktu, proyek website perlu perencanaan yang matang. Penelitian ini menerapkan metode Critical Path Method (CPM) dan Program Evaluation and Review Technique (PERT) pada sistem informasi manajemen untuk perencanaan dan penjadwalan proyek website akreditasi. CPM digunakan menentukan rangkaian aktivitas kritis proyek sedangkan PERT melakukan perhitungan durasi proyek probabilistik. Hasil penerapan menunjukkan sistem informasi mampu membantu manajemen proyek website akreditasi agar selesai sesuai tenggat waktu. Selain fitur perencanaan dan penjadwalan, sistem dilengkapi modul monitoring dan evaluasi capaian proyek. Dengan menerapkan CPM dan PERT pada sistem informasi manajemen proyek, perencanaan dan pengendalian proyek menjadi lebih terarah dan terpercaya.